Incidencia del nuevo sistema de evaluación en el rendimiento académico de los niños del segundo año de educación básica de la escuela Pedro Vicente Maldonado del cantón Pujilí en el periodo académico 2013-2014 - Manangón Muetecachi, Juan Fernando (2015)
This research work will carry out in order to determine the level of influence of the new learning evaluation system in the student’s academic performance, specifically on the children from second year of Vicente Maldonado Elementary School, at the same time, give to educational actors the guidelines to the correct use of new techniques and evaluation tools; so a correct learning estimation facilitates to choose a correct decision which will improve the teaching-learning process quality.